2022
DOI: 10.3389/fphar.2022.863082
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Prospects of Curcuminoids for the Remedy of COVID-19: Truth or Myth

Abstract: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is a positive-strand RNA virus, and has rapidly spread worldwide as a pandemic. The vaccines, repurposed drugs, and specific treatments have led to a surge of novel therapies and guidelines nowadays; however, the epidemic of COVID-19 is not yet fully combated and is still in a vital crisis. In repositioning drugs, natural products are gaining attention because of the large therapeutic window and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 220 publications
(253 reference statements)
0
13
0
Order By: Relevance
“…The severe inflammation and cytokine storms are the most fatal etiology of COVID-19. There are several scientific reports of phytocompounds can bind and affect COVID-19 relative cytokines pathways, such as curcumin, quercetin, kaempferol, and luteolin can form binding interaction with TNF, IL-6, NF-κB [92] , [93] , [94] . As anti-inflammatory role of dexamethasone, phytocompounds can also interfere cytokine production, affect inflammatory response and attenuate immunity but the less intense of adverse effect when compared with dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…The severe inflammation and cytokine storms are the most fatal etiology of COVID-19. There are several scientific reports of phytocompounds can bind and affect COVID-19 relative cytokines pathways, such as curcumin, quercetin, kaempferol, and luteolin can form binding interaction with TNF, IL-6, NF-κB [92] , [93] , [94] . As anti-inflammatory role of dexamethasone, phytocompounds can also interfere cytokine production, affect inflammatory response and attenuate immunity but the less intense of adverse effect when compared with dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“… 264 , 275 , 276 Given the restricted bioavailability of most polyphenols, the systemic effects of these phytocompounds have been ascribed to the gene-mediated antioxidative, anti-inflammatory, and immunomodulatory attributes that were exploited to defend host cells and mitigate illness severity in COVID-19. 3 , 277 It has been found that the antioxidant and antiviral activities are exerted in the gastrointestinal system where polyphenols are present in high concentrations. 277 The intake of fruits and vegetables can support and maintain a positive health status by overcoming oxidative stress, inflammation, as well as the associated pathologies.…”
Section: Polyphenolsmentioning
confidence: 99%
“…It has been shown that these phytocompounds can be involved in preventing and treating a series of chronic degenerative pathologies, including nutritional diseases, such as metabolic syndrome, type 2 diabetes mellitus, nonalcoholic fatty liver disease, insulin resistance, or atherosclerosis. Their pharmacological potential was also noticed in inflammatory lung diseases. , Moreover, polyphenols are endowed with inhibitory activity exhibited against viral components and actions. ,, Given the restricted bioavailability of most polyphenols, the systemic effects of these phytocompounds have been ascribed to the gene-mediated antioxidative, anti-inflammatory, and immunomodulatory attributes that were exploited to defend host cells and mitigate illness severity in COVID-19. , It has been found that the antioxidant and antiviral activities are exerted in the gastrointestinal system where polyphenols are present in high concentrations . The intake of fruits and vegetables can support and maintain a positive health status by overcoming oxidative stress, inflammation, as well as the associated pathologies.…”
Section: Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations